2020
DOI: 10.1186/s12883-020-01826-w
|View full text |Cite
|
Sign up to set email alerts
|

The Promotoer, a brain-computer interface-assisted intervention to promote upper limb functional motor recovery after stroke: a study protocol for a randomized controlled trial to test early and long-term efficacy and to identify determinants of response

Abstract: Background: Stroke is a leading cause of long-term disability. Cost-effective post-stroke rehabilitation programs for upper limb are critically needed. Brain-Computer Interfaces (BCIs) which enable the modulation of Electroencephalography (EEG) sensorimotor rhythms are promising tools to promote post-stroke recovery of upper limb motor function. The "Promotoer" study intends to boost the application of the EEG-based BCIs in clinical practice providing evidence for a short/long-term efficacy in enhancing post-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…The correlation between BCI accuracy and FMA improvement in this study indicated that BCI accuracy could influence training outcome in stroke patients, in agreement with previous reports [5,8,11]. The positive effect of BCI in post-stroke hand recovery is generally considered as the promotion of neural plasticity in previous studies [5,8,11,12,29]. The promising outcome of MI based BCI training to neurorehabilitation has been validated in a recent meta-analysis [30].…”
Section: Discussionsupporting
confidence: 89%
“…The correlation between BCI accuracy and FMA improvement in this study indicated that BCI accuracy could influence training outcome in stroke patients, in agreement with previous reports [5,8,11]. The positive effect of BCI in post-stroke hand recovery is generally considered as the promotion of neural plasticity in previous studies [5,8,11,12,29]. The promising outcome of MI based BCI training to neurorehabilitation has been validated in a recent meta-analysis [30].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning its potential to promote brain remodelling and structural restructuring, it has been widely applied in neurorehabilitation together with exoskeleton robots, functional electric stimulation, and other end-effectors [15,31,42,43]. Although, there was some heterogeneity among various studies, the effectiveness of BCI in motor recovery was worthy of affirmation [19,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…EEG is widely used because of its noninvasive, portability, and good temporal resolution. Researchers have demonstrated that MI-based BCI has the potential to be used in stroke rehabilitation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…They found a better clinical improvement in the NFB group with visual feedback compared to the MI group ( Pichiorri et al, 2015 ). Another ongoing study includes the same population from 1 to 6 months after stroke to evaluate the short and long-term efficacy of NFB training ( Mattia et al, 2020 ). They use visual ecological feedback with the participants’ own hands.…”
Section: Methodsmentioning
confidence: 99%
“…NFB training (Mattia et al, 2020). They use visual ecological feedback with the participants' own hands.…”
Section: Time-based Targetmentioning
confidence: 99%